Rice Growth and Production Response with Additional doses of Nitrogen and Sulfur Fertiliser in the Kashmir Valley - Mohammad Rafiq Khan; Waseem Raja; Tanveer Ahmad Ahngar; Raaqib Rasool Parray; Aadil Akbar Wani; Mohd Salim Mir; Zahida Rashid; Raies Ahmad Bhat; Tajalee Gulshan; Bisma Nazir (Archives of Current Research International, 2025)
Rice is a nutritional staple food which provides instant energy as its most important component is carbohydrate (starch). It provides about 700 calories per day per person for about 3000 million people living mostly in developing countries. Nitrogen influences rice yield by playing a major role in photosynthesis, biomass accumulation and spikelet formation. Furthermore, excessive use of high-analysis fertilisers in the recent past for improved cultivars has led to nutrient imbalance in soil, particularly to the deficiency of secondary nutrients like sulphur. Realising the importance of sulphur and nitrogen on growth and yield in rice, a field experiment was conducted at the Crop Research Farm of the Division of Agronomy, Faculty of Agriculture, Sher-e-Kashmir University of Agricultural Sciences and Technology of Kashmir during Kharif, 2021. The soil of the experimental field was silt clay loam with neutral pH, low in available nitrogen, medium in phosphorus, potassium and organic carbon, however, sufficient in sulphur. The experiment consisted of two factors: Factor A being Nitrogen Levels (kg ha-1) as Control, N60, N80, N120, and Factor B being Sulphur Levels (kg ha-1) as Control, S15, S30, S45 laid out in Factorial Randomised Complete Block Design with three replications. Plant height was recorded from the ground level to the tip of the tallest leaf during vegetative stages, and up to the tip of the tallest panicle at maturity. Economic analysis was performed based on prevailing input and output prices, computing gross return, net return, and benefit-cost ratio for each treatment. Significant variations in growth parameters, yield attributes, and yield were recorded among different levels of nitrogen and sulphur management practices under investigation. Significantly higher plant growth parameters, yield attributes, and yield were recorded in the 80 kg ha-1 level of nitrogen and the 30 kg ha-1 level of sulphur. Significant interaction was also seen between nitrogen (80kg N ha-1) and sulphur (30kg S ha-1) on panicle no m-2, filled grains per panicle and grain yield. Among the various treatments, treatment combination N2S2 (80kg N ha-1 and 30 kg S ha-1) revealed the highest B: C ratio of 2.23, followed by N3S3 (120kg N ha-1 and 45 kg S ha-1) with a B: C ratio of 2.22. For the final recommendation, the experimental findings should be validated at other locations in the Kashmir valley. The reduced application will reduce losses of different forms of nitrogen to surface water, ground water and to the atmosphere.